2017
DOI: 10.1103/physrevb.95.075119
|View full text |Cite
|
Sign up to set email alerts
|

Electronic correlations in vanadium revealed by electron-positron annihilation measurements

Abstract: The electronic structure of vanadium measured by Angular Correlation of electron-positron Annihilation Radiation (ACAR) is compared with the predictions of the combined Density Functional and Dynamical Mean-Field Theory (DMFT). Reconstructing the momentum density from five 2D projections we were able to determine the full Fermi surface and found excellent agreement with the DMFT calculations. In particular, we show that the local, dynamic self-energy corrections contribute to the anisotropy of the momentum den… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 74 publications
(102 reference statements)
1
9
0
Order By: Relevance
“…2D-ACAR exploits the annihilation of electron-positron pairs to investigate the electronic structure [5,6,19,49]. After implantation into the sample, positrons thermalize within a few picoseconds and subsequently propagate in Bloch states, as they also feel the crystal potential.…”
Section: D-acarmentioning
confidence: 99%
See 2 more Smart Citations
“…2D-ACAR exploits the annihilation of electron-positron pairs to investigate the electronic structure [5,6,19,49]. After implantation into the sample, positrons thermalize within a few picoseconds and subsequently propagate in Bloch states, as they also feel the crystal potential.…”
Section: D-acarmentioning
confidence: 99%
“…Furthermore, both techniques enable the analysis of magnetic materials by spin-resolved measurements. There are numerous examples of the application of ACAR and Compton scattering on different material classes, including elemental crystals [5][6][7][8][9], alloys [10,11], magnetic compounds [12][13][14][15][16][17][18][19][20], heavy fermions [21], and superconductors [22][23][24]. A review on the applications of both techniques can be found in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the current DFT, GGA(+U) calculations limit themselves to the independent particle model, which may well be the reason why the Weyl points are not resolved in the momentum density spectra. In recent studies we partly include dynamical Coulomb interactions effects upon the 2D-ACAR spectra at least for the electronic subsystem 6,40 . Further work along the lines to include the direct electron-positron interaction is in progress.…”
Section: Discussionmentioning
confidence: 99%
“…This is why we call our method the Direct Inversion Method (DIM). Similar approaches have been employed for 2D-to-3D reconstruction in 2D-ACAR [6,19,[29][30][31][32]. However, as all of those approaches use an entropy-like, non-linear regularization functional, iterative algorithms are required to find a reconstruction.…”
Section: Introductionmentioning
confidence: 99%